2019
DOI: 10.1007/s40091-019-00252-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a new structural configuration of a concrete barrier wall under the effect of blast loads

Abstract: In this study, a non-linear three-dimensional hydrocode numerical simulation was carried out using AUTODYN-3D, which is an extensive code dealing with explosion problems. A high explosive material (comp-B) is blasted against several concrete wall barriers. The model was first validated using referenced experimental tests and has shown good results. Several numerical models were carried out to study the effect of changing the shape of wall barrier from flat to convex curve and concave curve, and also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, for the scenario simulated in this paper, geometries with curvatures similar to those studied by Taha et al [15] and Attia et al [17] did not prove advantageous when compared with simpler geometries, for example, G1, G2a, and G7a. Regarding the top edge of the G1 wall, the results (Figure 15) showed a small variation between the values of overpressure peaks.…”
Section: Resultsmentioning
confidence: 43%
See 3 more Smart Citations
“…However, for the scenario simulated in this paper, geometries with curvatures similar to those studied by Taha et al [15] and Attia et al [17] did not prove advantageous when compared with simpler geometries, for example, G1, G2a, and G7a. Regarding the top edge of the G1 wall, the results (Figure 15) showed a small variation between the values of overpressure peaks.…”
Section: Resultsmentioning
confidence: 43%
“…Geometries with curved surfaces (concave and convex) were investigated with angles of 20º, 40º, 60º, and 80º, where the thickness was kept the same as the trapezoidal section. Analyzes similar to this one were also conducted by Taha et al [15] and Attia et al [17]; these researchers concluded that, in the scenario studied by them, a concave surface with a 60º curvature had a better performance in reducing overpressures in the region behind the wall.…”
Section: Cross Section Geometry Of Physical Protection Barriersmentioning
confidence: 75%
See 2 more Smart Citations